(untitled) (Bodhi Path, 2026)
Jataka narratives are a significant genre of Buddhist literature in which moral, social, and religious values are communicated through stories of the Buddha’s past lives. Although the primary objective of the Jatakas is to establish Buddhist ideals such as compassion (karuna), charity (dana), morality (shila), forgiveness (kshama), and truth (satya), these stories also clearly reflect the reality, mentality, and structural limitations of the contemporary society. Specifically in the context of women, Jataka literature exposes the patriarchal mindset of ancient Indian society, its apprehensions regarding women, and its moral expectations. The status of women in ancient Indian society was not static but constantly changing. While in the Rigvedic period women had the right to education, Vedic study, and participation in religious rituals, with the strengthening of the patriarchal system in the Later Vedic period, there was a gradual decline in women’s freedom. In the Buddhist period, the establishment of the Bhikkhuni Sangha (Order of Nuns) by the Buddha certainly opened doors for the spiritual upliftment of women, but an egalitarian view towards women could not fully develop at the social and psychological levels. Jataka literature was created against this conflicting background. In Jataka narratives, women appear in various forms—as mothers, wives, queens, courtesans, ascetics, celestial nymphs (apsaras), or virtuous women. In some instances, they are depicted as embodiments of morality, sacrifice, and compassion, while elsewhere they are portrayed as fickle, greedy, deceitful, and the motivating force behind male destruction. This dualistic portrayal of women is not accidental but is the result of the patriarchal structure of the contemporary society, the ascetic-centric religious view, the insecurity of the male mind, and narrative strategies for moral instruction. The objective of the present research paper is to analyze the status, role, and evaluation of women in Jataka narratives. An attempt has been made to understand how Jataka literature presents women as symbols of both moral ideals and moral crises. Furthermore, it discusses why this portrayal of women, while being a reflection of the contemporary social reality, also becomes a significant historical source for modern feminist discourse. Clarifying the multidimensionality, dialectics, and limitations of the perspective towards women in Jataka literature through this study is the primary goal of this research.